Acute effects of beetroot extract and resveratrol ingestion on cardiovascular and cardiac autonomic modulation recovery after moderate-intensity aerobic exercise in individuals with coronary artery disease: a triple-blinded, randomized, placebo-controlled trial - Gonzaga, Luana Almeida [UNESP] (2025)
Purpose: This study aimed to evaluate the acute effects of beetroot extract and resveratrol supplementation (isolated and combined) on cardiac autonomic modulation and cardiovascular parameters recovery after exercise in individuals with coronary artery disease (CAD). Methods: 14 males with CAD were submitted to 4 protocols consisting of 30 min (min) of rest, 30 min of aerobic exercise on a treadmill (60% of the heart rate reserve HRR), followed by 30 min of recovery. Before each protocol, the subjects consumed 500 mg of starch (placebo protocol), 500 mg of beetroot (beetroot protocol), or 500 mg of resveratrol (resveratrol protocol), or 500 mg of beetroot and 500 mg of resveratrol (combined protocol). Heart rate variability (HRV) indices and cardiorespiratory parameters were determined at different times during the protocols. Results: Regarding HR, significantly higher values about rest in the placebo protocol at all recovery moments (1st to 30th min) were observed. Significant differences were observed in the other protocols (beetroot, resveratrol and combined) from the first to the 20th min recovery. For SBP, significantly higher values concerning rest were observed at the first minute of recovery for all protocols. No differences were found for the HRV index between time and protocols. Conclusions: The single supplementation of beetroot and resveratrol (isolated and combined) did not alter HRV and cardiovascular parameter responses between protocols. The consumption of beetroot extract and resveratrol enhanced vagal modulation and heart rate recovery compared to rest.